The feelings of patients assisted with fun activities during the hemodialysis session - Renata Brites Teixeira; Zélia Marilda Rodrigues Resck (Rev Rene)
This study aims to capture the feelings generated by recreational activities during hemodialysis. We adopted a phenomenological qualitative approach, considering 12 patients who were doing hemodialysis in an average size general hospital, located in Alfenas Minas Gerais. An interview was opened with the following question. How do you feel about the recreational activities during the dialysis session? In all the interviewed people only positive feelings were expressed, like the following: happiness/joy, entertainment/fun, friendship and appreciation. The development of recreational activities proved to be beneficial arousing joy and laughter to brighten up the four hours of dialysis. The reports obtained show the importance of developing the bond and listening. The humanization established by extension activities as organizer in the care process allows the implementation of strategies for strengthening the process of care quality. The development of recreational activities proved to be beneficial, awakening joy, laughter and soothing the four hours of hemodialysis. The reports obtained show the importance of developing the bond of listening and of the humanization established by extension activities as organizer in the care process and also enables the implementation of strategies for strengthening the process of care quality.